Um estudo semiótico da experimentação filmada no ensino de Ciências: significações e ressignificações de conceitos sobre a combustão - Lira, Milton Basto (2021)
According to the theoretical framework proposed by Charles Sanders Peirce (1839-1914), using a investigative demonstrative approach, videos of experiments with candles were applied in classes for high school students in order to promote meanings and resignifications on the scientific concept of combustion. The recorded experimente can be an alternative to teachers that do not have suitable laboratories and conditions (materals and reagentes) in the school and, considering the context caused by the SARS-CoV-2 virus pandemic, cause of covid-19 disease, the filmed experiments are an excellent alternative for science education teachers to promote meanings and resignifications in distance learning. Permeating the levels of chemical knowledge (macroscopic, representational and submicroscopic), we explored the contents and concepts, tangled and relevant to the phenomenon of combustion, such as, for example, chemical reactions, composition of matter, physical states of matter, gases and their properties, mixtures, stoichiometry, flash point, flammability limit, pressure, temperature, acids, bases and pH. The analysis of the dialogues, writings and interjections produced by the students when they participated in the classes were carried out based on a semiotic theory of Charles Sanders Peirce. As a result, we checked that the students reached, by the end of the activities, meanings and resignifications of concepts and theories acquired during the process. We consider the methodology can be adapted and expanded to be applied at higher education level, being necessary future studies in this prism. Therefore, in this work, we defend the thesis that, using an investigative demonstrative approach, the application of filmed experiments to high school students, based on the theoretical framework proposed by Peirce (1983), can arouse genuine doubts and provide discussions that stimulate meanings and resignifications processes on scientific concepts involving combustion.